(3OjhGf GdMGLQis - (3GdMGLQi MSGe GdOjf YjSi Hf SfLQ Hf HgQGe GdCQHdi,J (B639 (3g` s
(3ChdgG (B:s
(3UaMI ai GdJYQja HGdMGLQi Ke bUjOI OGdjI jeOM ajgG Qcf GdOhdI CHj TgGH GdOjf hChdgG eGddg ehY JSjd Sjd GdQOGA CMOi HPcQ GdYGeQjI MGO s
(3BNQgG (B:s
(3jGef NWQ Gfg dbdHi ZeQJ gd JQLeY ai GdYJGH Jdc GdfcJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B25s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW s
Keywords: (3GdCOHs